Influence of contextual factors on turnover intention: examining the mediating role of civility - Shama Sadaqat; Ghulam Abid; Francoise Contreras (Cogent Business & Management, 2022)
In line with the organizational support theory, our study examined the influence of managerial support and perception of fairness on employees' turnover intention, and the mediating influence of workplace civility. Data was collected over a period of 2 months from 935 full-time employees (manufacturing and service sector) in two waves to minimize the common method bias. Our study finds that managerial support and fairness perception positively influence workplace civility. We also find that civility shows a vibrant role in clarifying the relationship between contextual factors (managerial support, perception of fairness) and turnover intention. Furthermore, we discuss the theoretical and practical implications along with future directions.
Keywords: 650; turnover intention; civility; fairness perception; managerial support